The equalizer 2 [videorecording (DVD)] - Washington, Denzel, 1954-; Pascal, Pedro; Pullman, Bill; Fuqua, Antoine (Sony Pictures Home Entertainment, 2018)
Robert McCall has rededicated his life to the pursuit of justice. But when his mission strikes close to home, he will be consumed by vengeance, seeking a revenge that knows no boundaries.